DNA‐Templated Silver Nanoclusters for Multiplexed Fluorescent DNA Detection. Issue 12 (10th December 2014) - Zhang, Ying; Zhu, Changfeng; Zhang, Lei; Tan, Chaoliang; Yang, Jian; Chen, Bo; Wang, Lianhui; Zhang, Hua
Abstract : Novel label‐free/conjugation‐free molecular beacons are designed based on DNA templated‐silver nanoclusters for multiplexed DNA detection. The assay is implemented in solution, which makes it easy for the in‐situ and real‐time analysis. This study demonstrates a new method for multiplexd detection of biological molecules by using fluorescent Ag nanocluster‐based molecular beacon probes.